PENGEMBANGAN ENSIKLOPEDIA DIGITAL BERBASIS SAINS KELAS IV SD NEGERI 159 PALEMBANG - Sapitri, Wira; Amir Hamzah; Ayu Nur Shawmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a science-based digital encyclopedia as a teaching material intended for fourth-grade students at SDN 159 Palembang. The background of this research is the lack of engaging, interactive, and student-centered teaching materials that meet the needs of students in understanding IPAS content, especially the theme of human sensory organs. Therefore, the development of this teaching material is expected to support the learning process at SDN 159 Palembang to become more effective. This research uses the Research and Development (R&D) method with the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. At the analysis stage, observations and interviews with educators were conducted to identify learning needs. The findings revealed that the learning process remained conventional and lacked the use of digital media. Consequently, a digital encyclopedia was developed based on the learning achievements of the Merdeka Curriculum. This product is presented in a digital format containing content material, attractive illustrations, and interactive features that support learning. Validation by subject matter experts, language experts, and media experts showed that this encyclopedia is highly valid with an average score of 96.3%. Practicality testing also showed very positive responses, with scores of 96% from educators and 83% from students.